Smartphone Usage and Communication Skills Among Higher Education Students: Structural Model - Yanuarto, Wanda Nugroho; Setyaningsih, Eka; Sriyanto, Sriyanto; Zakaria, Mohamad Ikram (Jurnal Pendidikan MIPA, 2024)
With the advent of smartphones, social communication has become much easier to enable than with previous generations of communication tools. Furthermore, it is essential to acknowledge the value of communication in assisting kids in developing relationships with their classmates. Objective: The primary purpose of this research was to examine the relationship between higher education students' smartphone usage and their deterioration in communication skills. Method: The data for this statistically designed study will be collected using a snapshot survey. Participating were 556 undergraduates, with the vast majority serving as pre-service teachers at Teacher Training and Education Faculty, Universitas Muhammadiyah Purwokerto, Indonesia. After that, AMOS version 24 was used to analyze the data even further. Findings: Students' communication skills were found to be positively correlated with their smartphone usage. The medium-sized association between effective communication skills and smartphone use. Extraordinary smartphone use among elementary school pupils may also affect their ability to communicate in real life, according to one reading of the results. Conclusion: Students who spend too much time on their phones are less likely to be good communicators, according to the research. Students should so exercise greater restraint when using their smartphone if we value effective communication abilities among them. Existing psychological theories from the era of information technology can benefit theoretically from this study.        Keywords: communication skills, higher education students, smartphone usage, and structural model. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp178-194